Decision Support System For Determining The Best Graduate Students Using The Analytical Hierarchy Process Method at STMIK Neumann - Simanjuntak, Berkat; siburian, Salomo (Jurnal Manajemen, Informatika, Rekayasa Perangkat Lunak dan Teknologi Komunikasi, 2024)
This study discusses determining the best graduate students, the process of determining the best graduate students is a problem that involves many criteria that are assessed, so that a decision support system is needed to solve it. The process of determining the best graduate students at STMIK Neumann is still constrained because there is no effective method yet and the assessment criteria are only based on GPA scores. In designing this system, researchers used the Analytical Hierarchy Process (AHP) method as the weighting method used. The four basic criteria used are GPA, scientific writing, superior achievement/ability and English. The AHP method can display the value of the priority weight of criteria that can be used as an alternative to determine the best graduate students. The decision support system application for determining the best graduate students is made using a desktop-based programming language, namely Visual Basic 2010 and MySQL as the database. The system built is able to provide ranking recommendations from the number of values sorted by the highest weight. With this system, it is hoped that it can provide an alternative for decision makers to determine the best graduate students at STMIK Neumann.